Clinical outcomes and performance indicators of patients with kidney failure and acute kidney injuries in ASEAN countries. Issue 9 (12th July 2022) - Tan, Jackson; Liew, Adrian; Koh, David
Abstract: Introduction: This review article reports clinical outcomes and performance indicators of patients with kidney failure (KF) and acute kidney injuries (AKI) in Association of South East Asian Nations (ASEAN) countries. Methodology: Association of South East Asian Nations data, segregated by income status, from national registries and literature were collated, compared and benchmarked against international references. Results: The national incidence and prevalence of treated KF ranged from 172 to 479 per million population (pmp) and 36–2255 pmp, respectively. Brunei (79%), Malaysia (66%) and Singapore (66%) had world‐leading proportions of diabetes‐related KF. Hemodialysis (HD), Peritoneal Dialysis (PD) and transplant accounted for 68–100%, 0–27% and 0–18% of all KF replacement therapy, respectively. Transplant patient survival was superior with 90%–93% at 5 years and 71%–90% at 10 years, compared to PD (44%–54%) and HD (53–64%) at 5 years. Higher‐income countries were able to achieve good anemia control, HD and PD adequacy targets, while usage of arteriovenous fistula in HD varied from 70% to 85%. Acute Kidney Injury rates ranged from 24.2% to 49.2% of high‐dependency admissions. Lower incidences of PD peritonitis and HD catheter‐related Bloodstream Infections; and PD‐favouring quality‐of‐life were evident in higher‐income countries. Conclusion: Association of South East Asian Nations has a challenging burden of kidney disease, with extremely high incidence, prevalence, DM‐related KF and AKI rates. The magnitude of the prevailing problem calls for the creation of a regional society under the auspices of ASEAN with a shared perspective of universal, equitable and charitable access to quality renal care; consistent with the founding premises and healthcare initiatives of ASEAN. SUMMARY AT A GLANCE: This review article provides a comprehensive summary on clinical outcomes and performance indicators of patients with kidney failure and acute kidney injury in ASEAN. Different income countries have varied presentations and outcomes of diseases, indicating a disparity in provision and access of renal services. Higher‐income countries have equivalent quality outcomes compared to developed countries, while lower‐income countries are more focused on enabling the basic provision of renal services to their population.